S-Nitrosated human serum albumin dimer as novel nano-EPR enhancer applied to macromolecular anti-tumor drugs such as micelles and liposomes - Kinoshita, R.; Ishima, Y.; Ikeda, M.; Kragh-Hansen, U.; Fang, J.; Nakamura, H.; Chuang, Victor; Tanaka, R.; Maeda, H.; Kodama, A.; Watanabe, H.; Maeda, H.; et al. (Elsevier, 2015)
© 2015 Elsevier B.V. All rights reserved. The enhanced permeability and retention (EPR) effect is a unique phenomenon of solid tumors, and it can serve as a basis for the development of macromolecular anticancer therapy. We have previously found that recombinant human serum albumin dimer, and especially its S-nitrosated form (SNO-HSA-Dimer), is an enhancer of the EPR effect. In this study, we investigated the influence of SNO-HSA-Dimer on the anti-tumor effect of two types of macromolecular anti-tumor drugs, namely N-(2-hydroxypropyl)methacrylamide polymer conjugated with zinc protoporphyrin, which forms micelles and can be used for fluorescence studies. The other was PEGylated liposomal doxorubicin (Doxil), a typical example of a stealth liposome approved for medical usage. In mice having C26 tumors with highly permeable vasculature, SNO-HSA-Dimer increases tumor accumulation of the drugs by a factor 3-4 and thereby their anti-tumor effects. Experiments with Evans blue revealed increased EPR effect in all parts of the tumor. Furthermore, SNO-HSA-Dimer improves the anti-metastatic effects of Doxil and reduces its minor uptake in non-tumorous organs such as liver and kidney. Tumor accumulation of Doxil in B16 tumors, which are characterized by a low permeable vasculature, increased even more (6-fold) in the presence of SNO-HSA-Dimer, and the improved accumulation lead to decreased tumor volume and increased survival of the animals. The administration of SNO-HSA-Dimer itself is safe, because it has no effect on blood pressure, heart rate or on several biochemical parameters. The present findings indicate that SNO-HSA-Dimer is promising for enhancing the EPR effect and consequently the specific, therapeutic effects of macromolecular anticancer drugs.